AN ANALYSIS OF INTERMEDIATE LEVEL CHEMISTRY STUDENTS’ OBSERVATIONS REGARDING THE CURRENT TEACHING PRACTICES IN CLASSROOM - Moeed, Swehra; Rauf, Prof.Muhammad; Seema, Shahzadi (Journal of Arts & Social Sciences, 2022)
To learn scientific concepts and to develop problems solving ability, students should be presented to an environment where inquiring and investigation is encouraged through interactive teaching approaches. To this consequence, a quantitative study is conducted to analyze intermediate level chemistry students’ observations regarding the current teaching practices in classroom. 680 students, 40 from eight Government Higher Secondary Schools (GHSSs) and 45 from eight Government Degree Colleges (GDCs) were selected randomly from all of Government Higher Secondary Schools and Degree Colleges. The study prevails the practice of traditional method while interactive approaches and use of audio-visual aids are more or less ignored consequently inquiry based interactive learning environment has not been achieved in classroom. Lack of accountability of teachers’ performance and shortage of required teachers in government institutes makes the situation worse. It has been suggested that interactive approaches and use of audio- visual aids should be promoted in order to develop problems solving ability in a science classroom. Dutifulness among teachers should be ensured through proper check, so as need to overcome shortage of teachers.